Thermal stability and oxidation resistance of architecturally designed Ti–Al–N- and Ti–Al–Ta–N-based multilayers - Koller, C.M.; Glatz, S.A.; Kolozsvári, S.; Bolvardi, H.; Mayrhofer, P.H. (Surface & coatings technology, 2020)
Omnipresent demands for enhanced mechanical properties under thermal load and increased oxidation/corrosion resistance trigger further developments of Ti1-xAlxN coatings. We here combine the beneficial alloying with Ta and architectural coating design by developing ~3-μm-thick Ti-Al-N/Ta-Al-N and Ti-Al-Ta-N/Ta-Al-N multilayers. Recently, we showed that especially the combination of 17–25 nm thin arc evaporated Ti0.55Al0.45N or Ti0.51Al0.43Ta0.06N layers with 3–4 nm thin reactively sputtered Ta0.77Al0.23N or Ta0.57Al0.43N layers leads to excellent properties in the as-deposited state. Here, we study their thermal stability in vacuum and ambient air in more detail. The multilayers clearly outperform their individual monolithically grown counterparts, Ti0.55Al0.45N, Ti0.51Al0.43Ta0.06N, Ta0.77Al0.23N, or Ta0.57Al0.43N during oxidation tests at 850 and 950 °C. From the latter, only the Ti0.51Al0.43Ta0.06N coating was not fully oxidised (the remaining nitride layer was ~1 μm) after the 25-h-oxidation treatment at 850 °C. However, after 25 h at 950 °C, also this coating was fully oxidised. The Ti0.51Al0.43Ta0.06N/Ta0.77Al0.23N multilayers even survived the 25 h–oxidation at 950 °C (~2 μm of the initial coating thickness still remaining). This multilayer also outperforms the other investigated coatings and multilayers with respect of mechanical properties after different annealing treatments in vacuum up to 1200 °C. Based on these results we can conclude that the combination of arc evaporated Ti0.51Al0.43Ta0.06N layers with sputtered Ta0.77Al0.23N layers (realised with an industrial hybrid process) not only leads to excellent mechanical properties after subject to thermal exposure but also excellent oxidation resistance. •Hybrid multilayer of arc evaporated and reactively sputtered TiAl(Ta)N and TaAlN layers.•Superior oxidation resistance of TiAlTaN/TaAlN-based multilayers•TiAlTaN/TaAlN-based multilayers survived even at 950 °C for 25 h in ambient air.